Soluble Triggering Receptor Expressed on Myeloid Cells 2 From Cerebrospinal Fluid in Sleep Disorders Related to Parkinson’s Disease - Mo, Mingshu; Tang, Yuting; Wei, Lijian; Qiu, Jiewen; Peng, Guoyou; Lin, Yuwan; Zhou, Miaomiao; Dai, Wei; Zhang, Zhiling; Chen, Xiang; Liu, Hanqun; Ding, Liuyan; et al. (Frontiers in Aging Neuroscience, 2021)
Background Triggering receptor expressed on myeloid cells 2 (TREM2) is a microglial receptor exclusively expressed in the central nervous system (CNS). It contributes to abnormal protein aggregation in neurodegenerative disorders, but its role in Parkinson’s disease (PD) is still unclear. Methods In this case-control study, we measured the concentration of the soluble fragment of TREM2 (sTREM2) in PD patients, evaluated their sleep conditions by the PD sleep scale (PDSS), and analyzed the relationship between sTREM2 and PD symptoms. Results We recruited 85 sporadic PD patients and 65 healthy controls without disease-related variants in TREM2. The concentration of sTREM2 in the CSF was significantly higher in PD patients than in healthy controls (p < 0.0001). The concentration of sTREM2 had a negative correlation with α-syn in the CSF from PD patients (r = 0.73, p = 0.0001). Receiver operating characteristic curve (ROC) analyses showed that sTREM2 in the CSF had a significant diagnostic value for PD (AUC, 0.834; 95% CI, 0.756–0.912, p < 0.05). The subgroup analysis showed that PD patients with sleep disorders had a significantly higher concentration of sTREM2 in their CSF (p < 0.01). The concentration of sTREM2 in the CSF had a positive correlation with the PDSS score in PD patients (r = 0.73, p = 0.0001). The ROC analyses showed that sTREM2 in the CSF had a significant diagnostic value for sleep disorders in PD (AUC, 0.834; 95% CI, 0.756–0.912, p < 0.05). Conclusions Our findings suggest that CSF sTREM2 may be a potential biomarker for PD and it could help predict sleep disorders in PD patients.